GYNECOLOGY AND REPRODUCTOLOGY, INNOVATIVE APPROACHES - Yusupov, S.O.; Rahmanova, N.X. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Gynecology and reproductology are rapidly evolving medical fields that address a wide range of issues affecting women’s reproductive health. From common gynecological disorders to complex infertility cases, diagnostic techniques and therapeutic strategies have significantly progressed. This paper presents a comprehensive overview of current diagnostic tools, traditional and modern treatment approaches, and recent innovations in gynecology and reproductology. Emphasis is placed on minimally invasive procedures, personalized medicine, and the integration of biotechnology in improving outcomes.